Analisis Residu Antibiotik Serta Kualitas Daging dan Hati Ayam Broiler Di Kabupaten Pidie Jaya Provinsi Aceh - Masrianto; Arief, I. I.; Taufik, E. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2019)
Chicken is one of the sources of animal protein which is widely consumed in Indonesia. The quality and safety of chicken meat for human health need to be considered. This chicken meat should be free from antibiotic residues. This study was aimed to determine antibiotic residues and qualty of meat and liver of chicken. The study used a total sample of 156 including 52 breast meat, 52 thigh and 52 liver obtained from 5 groups of chicken breeders in 5 sub districts of Pidie Jaya district (Meureudu,Ulee Gle, Bandar Baru, Trienggadeng and Meurah Dua). The pH average from tested chicken was found to be between 5.8 and 5.9. Cooking loss was found to be ranged from 33.28% to 39.42%. Antibiotic residues were tested by bioassay method. The Results showed that antibiotic residues were not detected in meat and liver except peniciline residues wich were found in breast meat, thigh and liver of chicken from Trienggadeng sub district.